A meta-analysis of mitral valve repair versus replacement for ischemic mitral regurgitation - Virk, Sohaib A. (Ann Cardiothorac Surg, 2015)
BACKGROUND: The development of ischemic mitral regurgitation (IMR) portends a poor prognosis and is associated with adverse long-term outcomes. Although both mitral valve repair (MVr) and mitral valve replacement (MVR) have been performed in the surgical management of IMR, there remains uncertainty regarding the optimal approach. The aim of the present study was to meta-analyze these two procedures, with mortality as the primary endpoint. METHODS: Seven databases were systematically searched for studies reporting peri-operative or late mortality following MVr and MVR for IMR. Data were independently extracted by two reviewers and meta-analyzed according to pre-defined study selection criteria and clinical endpoints. RESULTS: Overall, 22 observational studies (n=3,815 patients) and one randomized controlled trial (n=251) were included. Meta-analysis demonstrated significantly reduced peri-operative mortality [relative risk (RR) 0.61; 95% confidence intervals (CI), 0.47-0.77; I(2)=0%; P<0.001] and late mortality (RR, 0.78; 95% CI, 0.67-0.92; I(2)=0%; P=0.002) following MVr. This finding was more pronounced in studies with longer follow-up beyond 3 years. At latest follow-up, recurrence of at least moderate mitral regurgitation (MR) was higher following MVr (RR, 5.21; 95% CI, 2.66-10.22; I(2)=46%; P<0.001) but the incidence of mitral valve re-operations were similar. CONCLUSIONS: In the present meta-analysis, MVr was associated with reduced peri-operative and late mortality compared to MVR, despite an increased recurrence of at least moderate MR at follow-up. However, these findings must be considered within the context of the differing patient characteristics that may affect allocation to MVr or MVR. Larger prospective studies are warranted to further compare long-term survival and freedom from re-intervention.